Islamic Spiritual Well-Being as a Conceptual Framework for Islamic Education - Hidayatulloh, Muhammad Syarif; Suprayitno, Triyo; Fadil, Fadil (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This article develops Islamic Spiritual Well-Being (ISWB) as a conceptual framework for Islamic education. It examines the ontological foundations of the construct, the dimensions through which those foundations become educationally meaningful, and the points at which ISWB differs from established Western models. The study used qualitative library research and integrative conceptual analysis. Qur'anic verses, canonical Hadith, major works of Al-Ghazali, Al-Attas, Ibn Qayyim al-Jawziyyah, and Ibn 'Ata'illah al-Sakandari were read alongside contemporary scholarship on spirituality, Islamic psychology, and student well-being. Relevant propositions were documented, coded thematically, compared across sources, and synthesized into a conceptual structure. The analysis identifies three foundations Fitrah, Tawhid, and Khalifah—and five connected dimensions: Silah Billah, Tazkiyat al-Nafs, Maqasid al-Hayah, Ukhuwwah and Adab, and Sabr-Shukr. Rather than treating the relationship with Allah as a separate domain, ISWB places it within a tawhidic orientation that also shapes moral agency, purpose, social conduct, and resilience. The framework is offered as a theoretical basis for curriculum reflection, student guidance, and future scale development. Its educational and psychometric value, however, still requires empirical testing in diverse Islamic settings.